2011
DOI: 10.1128/aac.00706-11
|View full text |Cite
|
Sign up to set email alerts
|

Dose of Trimethoprim-Sulfamethoxazole To Treat Skin and Skin Structure Infections Caused by Methicillin-Resistant Staphylococcus aureus

Abstract: We undertook this study to investigate whether treatment with a higher dose of trimethoprim-sulfamethoxazole (TMP/SMX) led to greater clinical resolution in patients with skin and soft tissue infections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Another recent prospective observational study found no difference in outcomes among patients with MRSA SSTIs treated with TMP/SMX 2 DS PO twice daily vs. TMP/SMX 1 DS PO twice daily. 17 However, their patient population differed from ours both in the level of acuity (outpatient vs. inpatient care) as well as patient average weight/BMI (77e86 kg/ 28e30 vs. 101 kg/34). We further performed a subgroup analysis on TMP/SMX and clindamycin since: (1) these were the two most commonly prescribed oral antibiotics at discharge and (2) no pharmacokinetic data exists on their dosing in obese individuals.…”
Section: Discussionmentioning
confidence: 91%
“…Another recent prospective observational study found no difference in outcomes among patients with MRSA SSTIs treated with TMP/SMX 2 DS PO twice daily vs. TMP/SMX 1 DS PO twice daily. 17 However, their patient population differed from ours both in the level of acuity (outpatient vs. inpatient care) as well as patient average weight/BMI (77e86 kg/ 28e30 vs. 101 kg/34). We further performed a subgroup analysis on TMP/SMX and clindamycin since: (1) these were the two most commonly prescribed oral antibiotics at discharge and (2) no pharmacokinetic data exists on their dosing in obese individuals.…”
Section: Discussionmentioning
confidence: 91%
“…The high dose of TMP/SMX that was required for efficacy in this mouse model may be due the increased content of thymidine in mouse sera and tissues, which interferes with the activity of TMP (62). Since infected human tissues may also have increased thymidine levels, some studies have used high doses of TMP/SMX in treating CA-MRSA SSTIs in humans (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previously published studies, mice were administered subcutaneous (to the flank skin) or oral (via gavage) therapeutic doses of vancomycin (110 mg/kg administered subcutaneously twice daily) (30, 31) (Novaplus; Hospira, Inc., Lake Forest, IL), daptomycin (50 mg/kg administered subcutaneously daily) (32, 33) (Cubicin; Cubist Pharmaceuticals, Inc., Lexington, MA), linezolid (60 mg/kg administered subcutaneously and orally twice daily) (34) (Zyvox; Pfizer, Inc., New York, NY), clindamycin (100 mg/kg administered orally three times a day) (35,36) (Cleocin phosphate; Pfizer, Inc.), doxycycline (100 mg/kg orally twice daily) (33), and TMP-SMX (320/ 1,600 mg/kg administered orally twice daily) (37,38). Linezolid was used at the same dose for subcutaneous and oral administration because of equivalent bioavailability when given via either route (39).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trimethoprim-sulfamethoxazole can be used for the treatment of S. aureus infections such as uncomplicated SSTI [15][16][17]. Majority of our S. aureus isolates (77.1%) were sensitive to clindamycin, an important alternative to a beta-lactam antibiotic for S. aureus SSTIs [18,19].…”
Section: Discussionmentioning
confidence: 99%